Generation of monoclonal antibody against protein phosphatase 5 - Malanchuk, O.M.; Ovcharenko, G.V.; Tykhonkova, I.O.; Khoma, O.S.; Chorna, U.V.; Rybak, M.Yu.; Palchevskyy, S.S. (Вiopolymers and Cell, 2013)
Aim. Serine/threonine protein phosphatase 5 (PP5) is a unique member of serine/threonine phosphatase family, comprises a regulatory tetratricopeptide repeat (TPR) domain and regulates many cell signaling pathways. Here, we describe the development of a PP5 specific monoclonal antibody (mAb) and characterize its suitability for Western blotting and immunoprecipitation. Methods. Hybridoma technology has been used for monoclonal antibody generation. Immunization was carried out with recombinant mouse PP5 expressed in Escherichia coli as a GST-tagged fusion protein. Results. mAb against PP5 has been generated. Conclusions. Generated mAb specifically recognizes recombinant and endogenous mouse and rat PP5 and is suitable for Western blotting and immunoprecipitation. This mAb will be useful tool for investigations of PP5 physiological role. Мета. Серин-треонінова протеїнфосфатаза 5 (PP5) є унікальним членом родини серин-треонінових протеїнфосфатаз, оскільки містить регуляторні тетратрикопептидні повтори (TPR). PP5 бере активну участь у процесах сигнальної трансдукції. Описано процедуру отримання моноклональних антитіл, специфічних до PP5, а також особливості їхнього використання у Вестерн-блот аналізі та імунопреципітації. Методи. Гібридомну технологію застосовано для отримання моноклональних антитіл. Імунізацію проводили рекомбінантним злитим білком GST-таг, синтезованим у бактерійній системі. Результати. Одержано специфічні моноклональні антитіла проти РР5. Висновки. Моноклональні антитіла специфічно розпізнають рекомбінантну та ендогенну PP5 у Вестерн-блот анализі та імунопреципітації. Вони можуть стати необхідним інструментом при дослідженні фізіологічної ролі PP5. Цель. Серин-треониновая протеинфосфатаза 5 (PP5) является уникальным членом семейства серин-треонинових протеинфосфатаз, поскольку содержит регуляторные тетратрикопептидные повторы (TPR). PP5 активно участвует в процессах сигнальной трансдукции. Описаны процедура получения моноклональных антител, специфичных к PP5, а также особенности их использования в Вестерн-блот анализе и иммунопреципитации. Методы. Гибридомная технология применена для получения моноклональных антител. Иммунизацию проводили рекомбинантным слитым белкомGST-таг, синтезированным в бактериальной системе. Результаты. Получены специфические моноклональные антитела против РР5. Выводы. Моноклональные антитела специфично распознают рекомбинантную и эндогенную PP5 в Вестерн-блот анализе и иммунопреципитации. Они могут стать необходимым инструментом при исследовании физиологической роли PP5.